2014
DOI: 10.1097/dcr.0000000000000223
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Hysterectomy on Colonoscopy Completion

Abstract: Colonoscopy completion rates appear decreased in women with a history of hysterectomy, but the available literature is heterogenous. Further studies in this area are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…There is some evidence that prior hysterectomy may be associated with greater discomfort during intubation at colonoscopy, and lower cecal intubation rates. 57 Thus it has been suggested that women undergoing colonoscopic surveillance following hysterectomy undergo specific preprocedure counseling and measures to reduce procedural discomfort. 58…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that prior hysterectomy may be associated with greater discomfort during intubation at colonoscopy, and lower cecal intubation rates. 57 Thus it has been suggested that women undergoing colonoscopic surveillance following hysterectomy undergo specific preprocedure counseling and measures to reduce procedural discomfort. 58…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for gender differences in pain are not well understood [26 -28]. There may be biological dif-ferences; for instance, greater pain is observed in women who have had a hysterectomy [29,30]. On the other hand, studies have revealed that women expect more pain during flexible sigmoidoscopy compared to men [31], and it is possible that women are more willing to self-report pain compared to men [32].…”
Section: Discussionmentioning
confidence: 99%
“…A previous colorectal surgery was strongly associated to polyp retrieval failure. A previous hysterectomy has been related to incomplete colonoscopy, because of a higher frequency of loops and post‐operative fixations 19 . These mechanisms may also occur in patients with a previous colorectal surgery and interfere with the polyp retrieval ratio.…”
Section: Discussionmentioning
confidence: 99%
“…A previous hysterectomy has been related to incomplete colonoscopy, because of a higher frequency of loops and post-operative fixations. 19 These mechanisms may also occur in patients with a previous colorectal surgery and interfere with the polyp retrieval ratio. Of note: Although a previous colorectal surgery has been associated to inadequate bowel preparation, 20,21 these two factors were independent in the multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%